Consuming Korea: Global Branding and Soft Diplomacy from the Lens of K-Drama Cyber Travelers - Safira, Btari Anya; Badaruddin, Muhammad (Jobmark: Journal of Branding and Marketing Communication, 2024)
South Korea’s popular culture has been globalizing massively through various channels. Popular culture becomes a giant magnet that attracts global consumers to enjoy South Korea. Particularly by consuming k-drama, foreign consumers can expand their experience by doing internet-based-imaginary travel to South Korea’s landscape and daily cultures. This phenomenon is suitable for what we discuss later as the concept of cyber traveling. Departing from that point, this research focuses on South Korea’s global branding and soft diplomacy by analyzing k-drama’s cyber traveling experience by Indonesian consumers. We are using phenomenology as the main method, while in-depth interview, observation, and open-source document research are used as data collecting methods. This research found that k-drama consumption was able to facilitate cyber traveling that contributes significantly to South Korea’s global branding and soft diplomacy as a form of cultural globalization.